Wszyscy jesteśmy zdalnymi uczestnikami wojny. Analizy Jeana Baudrillarda jako podstawa wytwarzania humanistycznego oporu wobec konfliktów militarnych - Ilnicki, Rafał (Humaniora. Czasopismo Internetowe, 2024)
Jean Baudrillard presents provocative thesis that not only soldiers are participants in war but also people watching television are hostages to the ongoing military conflicts. The article will adress the genesis of this thesis based on the Baudrillard’s idea of virtuality of war that prevents from real war of happing, while at the same time obviously real war is taking place. This paradoxical situation will be the basis for both acknowledgment and criticism of Baudrillard’s interpretation of war. The main point of criticism is that Baudrillard erases people and at the same time is providing sophisticated analysis of people involved at different stateges of military conflicts. This leads to a lot of inconsistencies in Baudrillards thought. At the same time time Baudrillard refers to the humanistic goal of uncovering the real meaning of war behind what media create as illusion but this intelelectual perspective lacks in acknowledging his own position as an author and the freedom to think and act of viewers-hostages of media spectacle of war. In article there will presented a way of overcoming this cricis of passive remote viewer toward engaged humanistic approach which is available to people but on the condidition that they will want it to be important perspective in their lives.